Evaluating Teaching Assistance Programs Using the CIPP Model and Cognitive Apprenticeship Framework - Metafisika, Kartika; Abdillah, Husni; Chasanah, Uswatun (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study evaluates the Teaching Assistance program of a Madrasah Ibtidaiyah Teacher Education study program at an Islamic elementary school in Sidoarjo by integrating the CIPP (Context, Input, Process, Product) evaluation model with Cognitive Apprenticeship theory to assess professional identity formation. Utilising a qualitative case study design with the CIPP model of evaluation study, data were collected through document analysis, classroom observations, and structured interviews with key stakeholders, including the program head, field supervisors, preservice teachers as students’ tutees, and tutor teachers. Thematic analysis was conducted using an interactive model, employing CIPP as the macro-framework and the six pillars of Cognitive Apprenticeship as the analytical lens. The findings indicate that the Teaching Assistance Program successfully facilitated the transfer of expert pedagogical reasoning. The pillars of modelling, coaching, and scaffolding organically emerged, enabling preservice teachers to overcome initial culture shock and achieve independent classroom mastery. However, the current Learning Management System (LMS) primarily serves as a summative tool and lacks the interactive features needed to support the articulation and reflection phases fully. Integrating Cognitive Apprenticeship within the MBKM framework effectively fosters preservice teachers’ pedagogical reasoning. Upgrading the digital infrastructure to support asynchronous metacognitive reflection and providing specialised coaching for field supervisors are recommended to optimise the program.